ANALYSIS OF MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM) DEVELOPMENT ON COMPETITIVENESS DURING THE PANDEMIC PERIOD COVID-19 IN SUNGGAL DISTRICT DELI SERDANG REGENCY - Dhea Ranti Puspita; Ahmad Fadlan; Uswatun Hasanah (Universitas Kristen Indonesia Toraja, 2022)
The contribution of MSMEs to employment, both in developed and developing countries, including Indonesia, has a significant role in overcoming the problem of unemployment. The Covid-19 pandemic has resulted in a world economic recession of ups to -3.0%, 195 million people have lost their jobs and 420-580 million people have become poor (Maryanti et al., 2019). in the Sunggal sub-district itself, some of the problems that are often experienced by MSME business actors during the Covid-19 pandemic are the lack of use of technology, product innovation, the uneven distribution of local government social assistance to help capitalize business actors, as well as the decreasing amount of production due to a lack of interest in buying. the public during the pandemic, decreased the number of distributions, and decreased product quality because business actors lacked capital and income during this pandemic. Several business a were forced to increase product prices to cover existing production costs. The variables in this study are product innovation, capital, labor, technology, price, quality, production and distribution which are factors that influence the competitiveness of SMEs. This study aims to analyze the factors that affect the competitiveness of MSMEs in Sunggal District, Deli Serdang Regency. The data were processed using confirmatory analysis factor (CFA) then using multiple linear regression. the the data obtained from distributing the questionnaires were processed using SPSS Version 26.0 For Windows. the results showed that of the 8 variables analyzed, there were 3 factors that have the most influence, namely production factors, capital factors, and technology. Based on the multiple linear regression analysis, it shows that production, capital, and technology have a significant effect on the competitiveness of MSMEs, MSME a should b involved in the MSME development process in the midst of increasing competition, MSME actors must increase product innovation, and use technology to make it look more attractive to the public. so it can be superior to others.